1967
DOI: 10.1021/bi00856a014
|View full text |Cite
|
Sign up to set email alerts
|

The Autolytic Enzyme System of Streptococcus faecalis. II. Partial Characterization of the Autolysis and Its Substrate*

Abstract: A soluble autolysin has been isolated from cell walls of exponential (log) phase cultures of Streptococcus faecalis ATCC 9790 by means of gel filtration of trypsin-activated wall lysates. Trypsin and other proteolytic enzymes speed wall autolysis apparently by "activating" the autolysin. The autolysin seems to be closely associated with the wall as virtually complete wall dissolution is a prerequisite for obtaining the enzyme in solution. While the soluble autolysin can act on walls of S. faecalis and Micrococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(177 citation statements)
references
References 49 publications
8
169
0
Order By: Relevance
“…Thus, sensitivity to streptolysins was correlated with the presence of alanine-containing teichoic acids in streptococci (7). The specific autolytic activity of a staphylococcal mutant that is defective in teichoic acid was much lower than that of the wild type (8); sensitivity of Streptococcus faecalis cell walls to the homologous autolytic muramidase was somewhat decreased after the removal of teichoic acid (9). Pneumococcal cell walls "stripped" of their teichoic acid component lose sensitivity to homologous autolysin; cell walls in which the choline component of the teichoic acid was biosynthetically replaced by ethanolamine also become resistant to autolysin (2).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sensitivity to streptolysins was correlated with the presence of alanine-containing teichoic acids in streptococci (7). The specific autolytic activity of a staphylococcal mutant that is defective in teichoic acid was much lower than that of the wild type (8); sensitivity of Streptococcus faecalis cell walls to the homologous autolytic muramidase was somewhat decreased after the removal of teichoic acid (9). Pneumococcal cell walls "stripped" of their teichoic acid component lose sensitivity to homologous autolysin; cell walls in which the choline component of the teichoic acid was biosynthetically replaced by ethanolamine also become resistant to autolysin (2).…”
Section: Discussionmentioning
confidence: 99%
“…Recent assays of sterile competence factor-containing solutions prepared in complex media, as well as overnight culture fluids from CHALLIS organisms that lacked competence factor activity, revealed that these contained lytic activity against non-competent WICKY organisms. Since lysis of streptococcal organisms has always been a topic of interest to us and a number of other investigators (Barkulis, Smith, Boltralik & Heymann, 1964;Shockman, Pooley & Thompson, 1967, Coleman, van de Rijn & Bleiweis, 1970, and, since an extracellular lysin derived from group H organisms has never been before described, we undertook the survey to see whether the lysin was group or genus specific.…”
Section: Discussionmentioning
confidence: 99%
“…Shockman et al 3 ) reported that trypsin activated latent autolysin in Streptococcus jaecalis. The effects of trypsin on the autolysis of B. colisitnus have not been investigated yet, and the present paper deals with this problem.…”
Section: B )mentioning
confidence: 99%
“…3) reported that trypsin and other proteolytic enzymes accelerated wallautolysis, apparently by activating the latent autolysin. Trypsin-pretreatment of B. colistinus cells grown in glucose-bouillon medium enhanced the rate of autolysis and converted them into lysozyme-sensitive cells.…”
Section: Autolysis and Effect Ofproteolytic Enzymesmentioning
confidence: 99%